Electron Beam Welding and Characterization of Dissimilar Joints with TWIP Matrix Composites. Issue 5 (23rd October 2018) - Halbauer, Lars; Laubstein, Rudy; Radajewski, Markus; Buchwalder, Anja; Krüger, Lutz; Biermann, Horst
Abstract : Welding of Mg‐PSZ‐reinforced TWIP metal matrix composites (TWIP MMC) requires precise control over the level of dilution: otherwise, the risk of cavity formation arises. For this work, dissimilar joints between a TWIP MMC and an AISI 304 stainless steel are produced by means of electron beam welding over a wide range of process parameters. The influence of the welding process on the dilution, the microstructure of the welding seam, and the mechanical properties is presented and classified according to DIN EN ISO 13919–1. Furthermore, the welding quality of the samples is characterized by non‐destructive testing methods such as the novel uit and X‐ray analysis. It is shown that joints with EG ≥ 'C' can be produced with a high degree of reproducibility within a parameter window of Δx = 0.40.6 mm at welding speeds of 15 and 5 mm s −1 . The main defects are cavities, underfill, and lack of fusion which can all be detected by the uit down to a minimum defect size of 90–100 µm. Lower welding speeds and a slight underfocus decrease the tendency toward defects and for a (Δx) = 0.5 mm, tensile properties are achieved to match the level of the TWIP MMC. Abstract : Electron beam welding joints between a high alloy TWIP matrix composite and a AISI 304 steel are successfully produced. Various process parameters are studied in order to determine their effect on the number of welding defects. On the base of profound characterization, a set of parameters is identified, which produces joints that exceed the strength of the base material.